RESULTS OF FOOT PLANOVALGUS DEFORMITY SURGICAL TREATMENT IN CHILDREN WITH CEREBRAL PARALYSIS - Rakhman, P.M.; Korolkov, O.I. (World of Medicine and Biology, 2020)
Issues of treatment feet planovalgus deformity in children with cerebral palsy remain unresolved due to various structural, functional and biomechanical changes in the foot, as well as the complex pathogenesis of the disease formation. The purpose of the study was to present the results of retrospective analysis of surgical treatment of feet planovalgus deformity in children with cerebral palsy. Retrospective analysis was performed on case histories of 39 feet planovalgus deformity patients, with spastic type of cerebral palsy, who underwent surgical treatment in the period from 2002 to 2019. In Group 1, combined soft tissue interventions were used to correct feet planovalgus deformity, and in Group 2, in addition to the surgeries, interventions were performed aimed at correcting alignment in the joints of the hindfoot and midfoot. In Group 3, all children underwent combined surgery. Surgical treatment of feet planovalgus deformity in children with cerebral palsy aged 7-11 years, using techniques that are singularly aimed to correct contractures and tendon-muscle balance, is accompanied by a significant recurrence rate (66.7%). An algorithm for differentiated choice of methods for feet planovalgus deformity surgical treatment in children with cerebral palsy has been developed.